The effect of parental emotional abuse on the severity and treatment of PTSD symptoms in children and adolescents. (January 2021) - Hoeboer, Chris; de Roos, Carlijn; van Son, Gabrielle E.; Spinhoven, Philip; Elzinga, Bernet
Highlights: Emotional abuse was associated with more severe PTSD symptoms. PTSD symptoms significantly decreased during treatment. Emotional abuse has harmful consequences. Abstract: Background: Maltreatment by a primary caregiver is an important risk factor for the development of PTSD symptoms. Whereas meta-analyses indicate that parental emotional abuse is one of the most common forms of maltreatment, the impact of emotional abuse on PTSD symptoms and treatment effectiveness is still unclear, especially in children. Objective: We aimed to investigate the impact of parental emotional abuse on PTSD symptom severity and effectiveness of trauma treatment in children and adolescents. Method: In an outpatient sample ( N = 287, mean age = 15.5 years), emotional abuse, index traumatic event, and PTSD symptoms were assessed at baseline. Thereafter, patients received evidence-based treatment for trauma-related symptoms embedded in a broader (systemic) treatment package. In a subsample ( n = 130, mean age = 15.3 years) PTSD symptoms were assessed again 6 and 12 months after baseline. Results: Emotional abuse (rather than any other type of maltreatment) was associated with more severe PTSD symptoms in all symptom clusters. This was independent of whether emotional abuse was reported as index traumatic event or not. Moreover, PTSD symptoms were significantly reduced 6 months after the start of trauma-focused treatment, and emotional abuse was associated with more severe PTSD symptoms over the course of treatment. Conclusions: These findings underline the detrimental nature of emotional maltreatment in the context of PTSD symptomatology and treatment effectiveness. This calls for routine assessment of parental emotional abuse in the diagnostic phase, even when this is not the reason of referral.